IS THERE A RELATIONSHIP BETWEEN PHYSICAL ACTIVITY LEVEL AND CORE_x000D_ ENDURANCE? - POLAT, MİNE GÜLDEN; AKDUMAN, VEYSEL; SARI, ZÜBEYİR (My University, 2019)
Objective: The aim of this study was to determine the relationship between core endurance and physical activity level in healthy young adults.Methods: This study was conducted with 310 university students [male=154 (49.7%) and female=156 (50.3%)] aged between 17 and 28 whoattended Dokuz Eylul University. A sociodemographic data form was filled by all participants. Physical activity levels of the students were evaluatedusing the International Physical Activity Questionnaire (IPAQ). Core endurance was measured using anterior and right/left plank tests.Results: The average anterior plank test period of the participants was 77.0±43.8 sec. and the average lateral plank test period was 43.9±28.0 sec.We found that 14.8% (n=46) of the participants were inactive, 48.1% (n=149) were minimally active, and 37.1% (n=115) were very active,according to the IPAQ. According to the IPAQ data, vigorous physical activity, moderate physical activity, and walking variables in maleparticipants were significantly higher than female participants (p<0.05). Plank test periods (anterior and lateral) of participant which have vigorousand moderate physical activity was significantly higher (p<0.05).Conclusion: There was no statistically significant relationship between core endurance and physical activity level. According to this study, physicalactivity is not influenced by core endurance. Particularly, in order to protect or increase the endurance of the core muscles, which have an importantrole in the prevention of mechanical lumbar problems, it was thought that only physical exercises would not be sufficient and it should be performedspecial exercises for these muscles

Amaç: Bu çalışmanın amacı, sağlıklı genç erişkinlerde kor enduransı ile fiziksel aktivite seviyesi arasındaki ilişkiyi belirlemekti._x000D_ Yöntem: Bu çalışma, Dokuz Eylül Üniversitesi'nde okuyan yaşları 17 ile 28 arasında değişen 310 üniversite öğrencisiyle [erkek=154 (%49,7) ve_x000D_ kadın=156 (%50,3)] yapılmıştır. Sosyodemografik veri formu tüm katılımcılar tarafından doldurulmuştur. Öğrencilerin fiziksel aktivite düzeyleri_x000D_ Uluslararası Fiziksel Aktivite Anketi (UFAA) kullanılarak değerlendirildi. Kor enduransı ise anterior ve lateral plank testleri ile ölçüldü._x000D_ Bulgular: Katılımcıların ortalama plank test süresi 77,0±43,8 sn, ortalama yan plank test süresi ise 43,9±28,0 sn'dir. UFAA'ya göre, katılımcıların_x000D_ %14,8'i (n=46) inaktif, %48,1 (n=149) minimal aktif ve %37,1 (n=115) çok aktifti. UFAA verilerine göre erkek ve kız öğrenciler arasında şiddetli_x000D_ fiziksel aktivite, orta şiddetli fiziksel aktivite ve yürüme değişkenlerinde erkek katılımcıların skoru anlamlı olarak daha yüksekti (p<0,05). Şiddetli_x000D_ ve orta şiddetli fiziksel aktivite yapan katılımcıların plank test süreleri anlamlı olarak daha fazlaydı (p<0,05)._x000D_ Sonuç: Yapılan analizler sonucunda fiziksel aktivite seviyesi ile kor kasların enduransı arasında ilişki bulunamadı. Özellikle mekanik bel_x000D_ problemlerinin önlenmesinde önemli yeri olan kor kaslarının enduransının korunması veya artırılması için sadece fiziksel olarak aktif olmanın_x000D_ yetmeyeceği, bu kaslara yönelik özel egzersizlerin yapılması gerektiği düşünmüştür.
FİZİKSEL AKTİVİTE SEVİYESİ İLE KOR ENDURANSI ARASINDA İLİŞKİ VAR MIDIR?